Pengaruh Resilience Remaja Terhadap Penyalahgunaan Dadah - Wahyuni Ismail; Mostafa Kamal Mokhtar; Nasruddin Subhi; Fauziah Ibrahim (Fakultas Ushuluddin dan Filsafat Universitas Islam Negeri Alauddin Makassar, 2017)
Drug abuse behavior is one of part problem in the world need seriously treatment because very much the victims specially the teenagers. The aims of this research toexa mine the impact resilience with drug abuse and this research also seek to examine theimpact drug abuse according the gender. Quantitative method is kind of research. Data were obtained by administering a Resilence Scaleand Drug Abuse Screening Test. There are76 teenagers using drug as sample population. Data were analyzed by applying AnalyzisRegression using SPSS for Windows 21.00 program. The results indicated that therewere a significant (p=0,043) the impact to resilience with drug abuse among teenegers. Furthermore there was no significant (p = 0.110) the impact in drug abuse according gender